Assessment of Reactogenicity and Immunogenicity of the Quadrivalent Live Attenuated Influenza Vaccine - D. A. Lioznov; S. M. Kharit; M. K. Erofeeva; T. G. Zubkova; O. V. Gorchakova; S. L. Nikolaenko (Эпидемиология и вакцинопрофилактика)
In this multicenter double blind randomized clinical study with parallel groups conducted with 612 healthy volunteers, domestic influenza quadrivalent inactivated subunit vaccine Grippol® Quadrivalent safety, tolerability and immunogenicity was evaluated in comparison with seasonal trivalent vaccines, It was demonstrated that quadrivalent influenza vaccine Grippol® Quadrivalent possesses good tolerability, low reactogenicity, and has favorable safety profile similar to that for trivalent comparators. Besides, it was proven that quadrivalent influenza vaccine Grippol® Quadrivalent has same immunogenicity for three conventional strains and significantly exceeds trivalent comparators for missed influenza B strain.